Сучасні тенденції та перспективи розвитку нафтогазової освіти в контексті формування передумов інтелектуалізації діяльності суб’єктів національного господарства - Петренко, Віктор; Процюк, Василь; Кісь, Святослав; Petrenko, V.; Protsuk, V.; Kys’, S. (Східноєвропейський національний університет імені Лесі Українки, 2016)
Стаття присвячена актуальним проблемам взаємодії вищої нафтогазової освіти з виробничою сферою, ефективне функціонування якої, значною мірою залежить від рівня інтелектуального розвитку персоналу. На основі об’єктивного аналізу освітніх процесів в нафтогазовій галузі та авторських висновків розроблено рекомендації, спрямовані на активізацію взаємодії профільних ВНЗ з галузевими суб’єктами господарювання для досягнення цілей інтелектуалізації.The article is devoted to actual problems of interaction between the oil and gas field higher education and its production area, whose effective functioning depends largely on the intellectual level of its staff. The results of training, retraining and advanced training of employees in Ivano-Frankivsk national technical university of oil and gas are conducted using the facilities of core institutions of higher education for further intellectualization potential growth. Attention is drawn to low economic entities activity concerning the results of higher education core institutions knowledge application for actual problems solving in the oil and gas sector. The recommendations aimed at activation of core institutions of higher education cooperation process with enterprises for intellectualization goals achievement are given on basis of educational process objective analysis in the oil and gas sector and the author's opinion.
Modern trends and prospects of oil and gas education development within the context of preconditions forming of enterprises intellectual activity as national economy subjects
Keywords: нафтогазова освіта; oil and gas education; виробництво; персонал; інтелектуалізація; гармонізація; production; personnel; intellectualization; harmonization